2002
DOI: 10.1016/s0895-7061(01)02316-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tissue inhibitor of metalloproteinase-1 levels are elevated in essential hypertension and related to left ventricular hypertrophy

Abstract: The increased tissue collagen III levels found in the heart and vessels of hypertensive patients is due to a reduction in collagen degradation because of high TIMP-1 levels, rather than an increase in synthesis of collagen type III. The tissue source of this TIMP-1 is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 13 publications
3
27
1
Order By: Relevance
“…In this view, increased levels of TIMP-1 have been related to left ventricular hypertrophy. 20 Another finding of this study was the association of endothelial dysfunction with oxidative stress. We found decreased serum levels of antioxidants, especially vitamin C and selenium, and also decreased activity of erythrocyte glutathione peroxidase and superoxide dismutase.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this view, increased levels of TIMP-1 have been related to left ventricular hypertrophy. 20 Another finding of this study was the association of endothelial dysfunction with oxidative stress. We found decreased serum levels of antioxidants, especially vitamin C and selenium, and also decreased activity of erythrocyte glutathione peroxidase and superoxide dismutase.…”
Section: Discussionmentioning
confidence: 65%
“…9 In this view, several acute-phase reactants, soluble adhesion molecules, chemokines and metalloproteinases are altered in patients at risk of cardiovascular events, such as hypertensives, [13][14][15][16][17] diabetics 18 or those with left ventricular hypertrophy. 19,20 Moreover, in patients with coronary heart disease some of these serum markers have prognostic implications. [21][22][23] The aim of this study was to evaluate the correlation between the degree of endothelial dys-function, as measured by the maximal acetylcholine-induced forearm vasodilation, and the serum level of biochemical markers of inflammation, remodeling and oxidative stress, in a group of newly diagnosed, never-treated, essential hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among the stromelysins group, both MMP-3 and MMP-10 have similar substrate specificity, but MMP-3 has a higher proteolytic efficiency than that of MMP-10 (Visse and Nagase 2003). In hypertensive subjects, plasma MMPs and their TIMPs were increased and associated with LVH and LVDD (Lindsay et al 2002;Timms et al 2002;Tayabjee et al 2004). Therefore, we selected two different members of MMPs family to investigate their role in hypertensive LVH and LVDD.…”
Section: Measurement Of Plasma Mmps Concentrationsmentioning
confidence: 99%
“…Changes in the structure of the cardiac extracellular matrix (ECM) can impede left ventricular filling during diastole, and possibly contribute to symptomatic diastolic dysfunction. Indeed, it has been reported that circulating matrix metalloprotienase-9 level and tissue inhibitor matrix metalloprotienase-1 levels are higher in hypertensive subject than controls, and tissue inhibitor matrix metalloprotienase-1 levels are associated with left ventricular hypertrophy (LVH) and left ventricular diastolic dysfunction (LVDD) in some but not all studies (Laviades et al 1998;Li-Saw-Hee et al 2000;Lindsay et al 2002;Timms et al 2002;Tayabjee et al 2004).…”
mentioning
confidence: 99%
“…ACEi/ARB and spironolactone therapy have been shown to partly reverse the abnormal metabolism of cardiac collagen tissue and enhance cardiac function in ICM patients. 16,19,[22][23][24] Improvements in haemodynamics and electromechanical synchronization after CRT appear to be related to corrected collagen metabolism. 25,26 However, no clinical observations of the effect of CRT on collagen metabolism in ICM have previously been reported.…”
Section: Discussionmentioning
confidence: 99%